PENGARUH KINERJA AUDITOR, TURN OVER INTENTION, DAN KOMITMEN ORGANISASI TERHADAP PREMATURE SIGN- OFF (Ditinjau dari Goal Setting Theory) (Proceeding Fakultas Ekonomi, 2012)
Goal Setting Theory in this study is used to review and analyze the influence of internal individual factors (such as auditor individual performance, turnover intention and organizational commitment) on acceptance of a premature sign-off. Source of data in this study were auditors working in audit firms in Indonesia as respondents. The data was collected using survey method by sending questionnaires to the respondents by mail. The result of this study has shown that individual performance and turnover intention have influence to acceptance of a premature sign-off. On the other hand organizational commitment has no influence to acceptance of a premature sign-off. Keywords: Goal Setting Theory, Auditor Performance, Turnover Intention, Organizational Commitment, and Premature Sign-off.